Model for the Development of Information and Analytical Competence of Library Specialists: Results of a Pedagogical Experiment - I. I. Ryabova (Библиосфера, 2025)
Information and analytical competence (IAC) is one of the key professional competencies of a librarian. Its high level of proficiency allows librarians to effectively find relevant information and data, evaluate them, process, interpret and promptly present them in accordance with user preferences. Despite the fact that various aspects of information and analytical activities are reflected in scientific publications on the topic, the issue of developing the IAC of a library specialist remains poorly investigated. In library professionology and the theory of library and information education, there is no definition that clarifies the specifics of such competence. The purpose of the study is to experimentally test the author model for developing information and analytical competence of library specialists, necessary for the implementation of informing library users on popular issues in the web environment. The author, using terminological analysis, clarifies the definition of the IAC of library specialists that is necessary for the creation of information products on popular issues, which is open science. The work also defines the directions for the formation of the IAC and, on their basis, the model for the development of the IAC of a library specialist is developed, including target, conceptual, content, technological, evaluation and result blocks and the necessary pedagogical conditions. At the end of the study, the results of a pedagogical experiment, that confirm the effectiveness of the proposed model, are presented.